The Battle for Hearts and Minds: The Struggle for Power in Latvia in Early 1919 - Kārlis Dambītis (Acta Historica Universitatis Klaipedensis)
In early 1919, Courland, which had already been semi-abandoned during the First World War, turned into an area of the Baltic region where at least four political agendas, and, in many cases, the military forces that supported them, clashed. The Bolsheviks exported their world revolution and acted through the Army of Soviet Latvia. The German armed forces had withdrawn from parts of Estonia and Latvia, and were still under the command of Berlin. Volunteer units formed with the help of the German army, many of which included local Baltic Germans. The Latvian Provisional Government and the units loyal to it was under the command of Lieutenant-Colonel Oskars Kalpaks. All these forces needed motivated soldiers and loyal civilians who might become engaged in military activities. The article discusses the political, economic and social backgrounds that contributed to the motivation of soldiers and the public support for the warring parties, with a particular focus on how important the sense of belonging and identity was in these circumstances.